If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 5L Solving 12 = 5L Solving for variable 'L'. Move all terms containing L to the left, all other terms to the right. Add '-5L' to each side of the equation. 12 + -5L = 5L + -5L Combine like terms: 5L + -5L = 0 12 + -5L = 0 Add '-12' to each side of the equation. 12 + -12 + -5L = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -5L = 0 + -12 -5L = 0 + -12 Combine like terms: 0 + -12 = -12 -5L = -12 Divide each side by '-5'. L = 2.4 Simplifying L = 2.4
| 40=10y+8 | | 0.2R-1=0 | | 9+4t=30 | | 5x+2y+10z=39 | | 6(v-7)=8v+42 | | 3+987654-256= | | 3+987654-2566222= | | 3+987654-25664= | | 3-21y-24y^2= | | 14x^2+33x+10= | | -rt^3-r^3t= | | r^2+33r+90= | | 2a^2-7a-15= | | 2v^3+18v^2+40v= | | n-n^5= | | k^2+k-110= | | -x+y-z=2 | | 5x^4-10x^2+1=0 | | 12=-20-23x/10 | | 3x-y+2z=3 | | 200=600(a+1)/24 | | d=500(4+1)/24 | | 3/4(3t-4)=15 | | 4x+3y=34 | | y+1(27-6)+2=2 | | 8(5)+8-4(5)-3= | | 4x+1=-13-8x | | -4(3)(1/2)+3(-3)= | | (5)(-3)(-2)= | | -25-6x=-5-9x | | f(-x)=-(7-2x) | | 26=26-(8+3w) |